DAMPAK YURIDIS WANPRESTASI DALAM PERJANJIAN LEASING KENDARAAN BERMOTOR (STUDI PUTUSAN NOMOR 04/PDT.G.S/2021/PN PTI) - Jackson, Michael; Indiraharti, Novina Sri (Tribuere, 2024)
As the economy of a country develops, the needs of society will also increase. The needs of society, whether primary, secondary, or tertiary, will inevitably rise, including the need for transportation. To meet the transportation needs, many people obtain the necessary funds through borrowing. The high demand for financing among the public has led to the increasing number of financial institutions, both banks and non-bank financial institutions, with the goal of fulfilling the public's needs, especially for financing, whether in the form of funds or capital goods. With the existence of consumer financing, there is a need for legal regulations that can ensure security for both parties. Therefore, these regulations and legal foundations are governed by Law No. 42 of 1999 concerning Fiduciary Guarantees. This study focuses on a case ruling regarding default (wanprestasi) related to fiduciary guarantees, which took place in the Pati District Court, with ruling Number 04/Pdt.G.S/2021/PN Pti. The issue in this research is the default on a motor vehicle loan made by the debtor, Suratmi, to the creditor, PT Indomobil Finance Indonesia. The purpose of this research is to examine the legal consistency regarding the default ruling in Case Number 04/Pdt.G.S/2021/PN Pti. Therefore, this research aims to provide conclusions on the default issue between Suratmi and PT Indomobil Finance Indonesia, particularly whether the elements of default have been met and whether the case is in accordance with the applicable laws and regulations in Indonesia.